PENERAPAN METODE BERCAKAP-CAKAP DALAM MENGEMBANGKAN KEMAMPUAN BAHASA LISAN ANAK USIA DINI - Fatimah, Dayang; R, Marmawi; Linarsih, Andini (Universitas Tanjungpura, 2023)
Spoken language is an activity of expressing thoughts, ideas, and feelings of children, spoken language is very important for children so that children are more courageous to speak and interact with peers and people around them so it is very important to develop, to develop oral language skills, appropriate methods are needed . This study aims to describe the application of the conversation method in developing oral language skills in children aged 5-6 years at Kindergarten. This research method is descriptive in the form of qualitative research. The data sources for this study were 2 B1 class teachers, 15 B1 class children, and 1 B1 class child's parents. The research was conducted at Kindergarten. The research was conducted using three techniques, namely observation techniques, interview techniques and documentation techniques. The results of the study show that the application of the conversational method in developing oral language skills in children aged 5-6 years at teachers use the conversational method in developing oral language skills of children aged 5-6 years, the application of the conversational method Proficiency is carried out through questions and answers between the teacher and children, conversation activities are carried out when teaching in class and outside the classroom. From the application of the conversation method, the child's oral language skills are increasingly developing, the child becomes more courageous to speak and express his wishes, and the child can interact and socialize with teachers and peers.